1996
DOI: 10.1016/s0194-5998(96)70139-0
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Deficits in Deaf Children

Abstract: Considerable knowledge has been accumulated regarding acquired and congenital deafness in children. However, despite the intimate relationship between the auditory and vestibular systems, data are limited regarding the status of the balance system in these children. Using a test population of 15 children, aged 8 to 17 years, we performed electronystagmography testing. The test battery consisted of the eye-tracking (gaze nystagmus, spontaneous nystagmus, saccade, horizontal pursuit and optokinetic) tests, posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 6 publications
(9 reference statements)
3
52
0
3
Order By: Relevance
“…Potter and Silverman observed hypoactive (postrotatory) vestibular responses in just under 60 % of their test population, 34 deaf children [9] whereas Horak et al (1988) cite a figure of 66 % [6]. Selz et al also describe a significant difference in the vestibular function of deaf and hearing children (with reference to rotatory tests) ( [12]. Horak et al (1988) report a strong correlation between VOR tests (postrotatory in this study) and performance in the SOT.…”
Section: Caloric Excitabilitysupporting
confidence: 49%
See 1 more Smart Citation
“…Potter and Silverman observed hypoactive (postrotatory) vestibular responses in just under 60 % of their test population, 34 deaf children [9] whereas Horak et al (1988) cite a figure of 66 % [6]. Selz et al also describe a significant difference in the vestibular function of deaf and hearing children (with reference to rotatory tests) ( [12]. Horak et al (1988) report a strong correlation between VOR tests (postrotatory in this study) and performance in the SOT.…”
Section: Caloric Excitabilitysupporting
confidence: 49%
“…This hypothesis is supported by studies which show that vestibular dysfunction has a high frequency (up to 80 %) in children with severe hearing impairment [7][8][9][10][11][12][13]. The methods used involved assessment of either postrotatory or caloric nystagmus.…”
Section: Introductionmentioning
confidence: 94%
“…[20][21][22][23][24][25] This is under recognised. These children have delayed motor skills or may be described as 'clumsy'.…”
Section: Help For Balancementioning
confidence: 99%
“…Previous studies have found that 49-95% of children with hearing loss suffered from vestibular dysfunction, with the incidence increasing with the degree of hearing loss (Selz et al 1996). The cochlear and vestibular systems are anatomically and functionally connected, and so damage to either the cochlear or vestibular systems, or both, can lead to vestibular disorder and associated balance dysfunction (Rine et al 2000).…”
Section: Introductionmentioning
confidence: 99%